CASE STUDY: THE ROLE OF LEARNING STRATEGIES, PERSONALITY AND MOTIVATION IN THE SECOND LANGUAGE ACQUISITION: WRITING PROFICIENCY OF A SOMALIAN STUDENT - Ulin Ni’mah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The study aims to investigate a case study of second language acquisition of a foreign learner studying at Universitas Islam Negeri Maulana Malik Ibrahim, Malang. There are three aspects examined by the researcher such as the learning strategies, personality, and motivation which influence the learner’s second language acquisition of English. The findings of the research show that the subject has good learning strategies such as reading English books, learning via online media, and studying with friends. The subject has a good personality, an introvert who is confident in practicing English with several people in Indonesia. The subject has high motivation in learning English to get the scholarship and to have a good career in the future. After assessing his essay with the rubric score, the students’ writing proficiency is improved.